Microemulsions: Breakthrough Electrolytes for Redox Flow Batteries - Barth, Brian A.; Imel, Adam; Nelms, K. McKensie; Goenaga, Gabriel A.; Zawodzinski, Thomas (Frontiers in Chemistry, 2022)
Aqueous and non-aqueous redox flow batteries (RFBs) have limited energy and current densities, respectively, due to the nature of the electrolytes. New approaches to electrolyte design are needed to improve the performance of RFBs. In this work, we combined a highly conductive aqueous phase and an organic redox-active phase in a microemulsion to formulate a novel RFB electrolyte. As a proof-of-concept, we demonstrate an RFB using this microemulsion electrolyte with maximum current density of 17.5 mA·cm−2 with a 0.19M posolyte and 0.09M negolyte at a flow rate of only ~2.5 mL·min−1, comparable to early vanadium electrolyte RFBs at similar flow rates on a per molar basis. The novel active negolyte component is an inexpensive oil-soluble vitamin (K3). By combining aqueous and organic phases, the solvent potential window and energy density may be increased without sacrificing current density and new redox couples may be accessed. Microemulsion electrolytes show great promise for improved performance and increased energy densities in aqueous RFBs but the path forward is complex. We end with discussion of areas that need work to achieve the potential of these electrolytes.